Pengaruh Lingkungan Kerja, Kompensasi dan Motivasi terhadap Kinerja Karyawan pada Perusahaan Daerah Air Mineral (PDAM) Kabupaten Malang - Pijay fauzan; Sri Wilujeng; Arien Anjar Puspitosari Suharso (Jurnal Riset Mahasiswa Manajemen, 2018)
Human resource management is part of organizational management that focuses on the elements of human resources. The success of an organization in achieving organizational goals is determined by employee performance. The ability of employees to do the work for which they are responsible is a benchmark for achieving organizational goals. Employees in achieving organizational goals have responsibilities that must be completed by employees who are given the responsibility to complete them. Factors that also affect employee performance are the work environment, compensation and motivation. The purpose of this study was to determine the effect of the work environment, compensation and motivation. To determine the effect of the work environment on employee performance, to determine the effect of compensation on employee performance and to determine the effect of motivation on employee performance in the Regional Water Supply Company (PDAM) of Malang Regency. This type of research is quantitative. Then use probability sampling techniques. This study used a sample of 86 respondents taken from employees of the Regional Water Supply Company (PDAM) of Malang Regency. The data analysis technique used is multiple linear regression analysis techniques. The results of this study indicate that the work environment of compensation and motivation has a significant influence on employee performance.